No. -4+1/5= -3 4/5=-3.8 or -19/5
Unless g(x)=(2x+1)/5 which in case then you would be right.
Given that g(x)= 2x+1/5 and f(x)=x+4
Calculate the value of g(-2)
2(-2)+1/5= -3/5
Is this right??
How do i write an expression for gf(x) in the simpliest form??
And how do i find inverse functions such as g`1(x)?
2 answers
I noticed that Marth already gave you an answer correctly following the order of operation the way you typed it.
You followed the same order in finding g(-2) but made an arithmetic error.
g(-2) = 2(-2) + 1/5
= -4 + 1/5
= -19/5
Perhaps you meant
g(x) = (2x+1)/5
If so, follow Marth's steps using the corrected function for both g(f(x)) and the inverse of g(x)
You followed the same order in finding g(-2) but made an arithmetic error.
g(-2) = 2(-2) + 1/5
= -4 + 1/5
= -19/5
Perhaps you meant
g(x) = (2x+1)/5
If so, follow Marth's steps using the corrected function for both g(f(x)) and the inverse of g(x)